2022
DOI: 10.1111/ene.15359
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological, histopathological, and biochemical evaluation of the protective effect of probiotic supplementation against pentylenetetrazole‐induced seizures in rats

Abstract: Background and purposeResearch on the relationship between the gut microbiome and epilepsy is accumulating. The present study was conducted to evaluate the effect of probiotic supplementation on pentylenetetrazole (PTZ)‐induced seizures in rats.MethodsTwenty‐one adult male Wistar albino rats were included. The animals were divided into three groups of seven rats. Group 1 was a control group, whereas Group 2 rats received PTZ treatment and Group 3 rats had PTZ+PB (probiotic) treatment. For 6 weeks, Groups 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…For example, Wang et al ( 2022 ) found that probiotic supplementation reduced spontaneous seizure in the kainic acid-induced epilepsy model and the effect was accompanied with decreased level of inflammatory cytokines (IL-1 β, IL-6, and TNF-α), lipid peroxidation, DNA damage, and increased total antioxidant ability in the hippocampus. Decreased brain levels of IL-6, TNF-α, and nitric oxide following probiotic treatment were also reported in WAG/Rij rats (Aygun et al 2022b ) and in rats subjected to the PTZ seizure test (Aygun et al 2022a ). In a study by Wang et al ( 2019b ), L. helveticus R0052 exhibited anti-inflammatory properties by downregulating TLR2, TLR4, TLR5, NF-κB, and TNF-α transcription in liver, decreasing proinflammatory cytokines (IL-2, IL-6, IL-12, IL-17, TNF-α, RANTES, and MIP-3α) in serum, and enhancing the intestinal barrier of d -galactosamine-treated rats.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…For example, Wang et al ( 2022 ) found that probiotic supplementation reduced spontaneous seizure in the kainic acid-induced epilepsy model and the effect was accompanied with decreased level of inflammatory cytokines (IL-1 β, IL-6, and TNF-α), lipid peroxidation, DNA damage, and increased total antioxidant ability in the hippocampus. Decreased brain levels of IL-6, TNF-α, and nitric oxide following probiotic treatment were also reported in WAG/Rij rats (Aygun et al 2022b ) and in rats subjected to the PTZ seizure test (Aygun et al 2022a ). In a study by Wang et al ( 2019b ), L. helveticus R0052 exhibited anti-inflammatory properties by downregulating TLR2, TLR4, TLR5, NF-κB, and TNF-α transcription in liver, decreasing proinflammatory cytokines (IL-2, IL-6, IL-12, IL-17, TNF-α, RANTES, and MIP-3α) in serum, and enhancing the intestinal barrier of d -galactosamine-treated rats.…”
Section: Discussionmentioning
confidence: 70%
“…The second study showed that administration of probiotics after birth may decrease rotavirus-associated seizures in neonates (Yeom et al 2019 ). In animal studies, probiotics treatment reduced acute penicillin- (Kızılaslan et al 2022 ) and PTZ-induced seizures (Aygun et al 2022a ; Kilinc et al 2021 ), suppressed development of PTZ-induced kindling (Bagheri et al 2019 ; Tahmasebi et al 2020 ), ameliorated spontaneous seizures after kainic acid-induced status epilepticus (Wang et al 2022 ), and alleviated absence seizures in WAG/Rij rats with absence epilepsy (Aygun et al 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…The intervention resulted in a decrease in epileptic activity levels, a significant reduction in seizure severity, and a partial improvement in spatial learning and memory in the epileptic rats. Importantly, the probiotic treatment also led to decreased concentrations of pro-inflammatory cytokines IL-6 and TNF-α, reduced levels of nitric oxide (NO) and malondialdehyde (MDA), increased total antioxidant capacity (TAC), and elevated levels of GABA in the brain tissue (Bagheri et al, 2019;Aygun et al, 2022a;Aygun et al, 2022b). Additional research utilizing animal models of epilepsy has corroborated the anti-seizure effects of probiotics.…”
Section: Fmt Probiotics and Epilepsy Treatmentmentioning
confidence: 94%
“…VSL#3 reduced seizure severity and decreased proinflammatory cytokines that increase BBB permeability, elevate CNS cytokine levels, and increase neuronal excitability. VSL#3 also restored the increased total oxidant status in the brain [ 157 ]. The most recent study using VSL#3 induced focal seizures in rats via penicillin G. VSL#3 increased the latency and decreased the spike frequency of focal seizures, while decreasing proinflammatory cytokines and oxidative factors such as NO [ 158 ].…”
Section: Potential Dietary Treatments: Pro/prebioticsmentioning
confidence: 99%